1986
DOI: 10.1897/1552-8618(1986)5[917:aaceow]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Acute and Chronic Effects of Water Quality Criteria-Based Metal Mixtures on Three Aquatic Species

Abstract: Acute and chronic toxicity tests were conducted with three aquatic species to determine the effects of metals combined as mixtures at proposed water quality criteria concentrations and at multiples of the LC50 and maximum acceptable toxicant concentration (MATC) obtained from tests on six metals. These studies were the first part of a larger research effort to derive water quality criteria for combined pollutants by the U.S. Environmental Protection Agency.Arsenic, cadmium, chromium, copper, mercury and lead c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
69
1
1

Year Published

1997
1997
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(73 citation statements)
references
References 12 publications
2
69
1
1
Order By: Relevance
“…All measured dissolved concentrations are well below a 48-h NOEC [21] and a 30-d maximum allowable toxicant concentration (MATC) [23] reported for P. promelas. Overall, Cr would not be expected to be of toxicological concern because the measured concentrations in the 100% elutriates were more than 11 times lower than the CCC and 1,000 times lower than a MATC reported in the literature.…”
Section: Chromiummentioning
confidence: 53%
“…All measured dissolved concentrations are well below a 48-h NOEC [21] and a 30-d maximum allowable toxicant concentration (MATC) [23] reported for P. promelas. Overall, Cr would not be expected to be of toxicological concern because the measured concentrations in the 100% elutriates were more than 11 times lower than the CCC and 1,000 times lower than a MATC reported in the literature.…”
Section: Chromiummentioning
confidence: 53%
“…Note that these sums function as a unit of additive toxicity, except that values greater than 1 are not symmetrical with values less than 1 (Spehar and Fiandt, 1986). For example, in our tests a value of 6 would indicate that there would be no interaction because six toxicants made up the mixture; however, values of 0.5 and 3.0 would be equally more than additive and less than additive, respectively, since they are midway between 0 and 1, and 0 and 6.…”
Section: Mixture Toxicity Experimentsmentioning
confidence: 99%
“…Attempts to model the joint action of chemicals have already been made for the freshwater environment (Altenburger et al, 1990;Drescher and Boedeker, 1995;Spehar and Fiandt, 1986). The toxicity of a mixture of chemicals with a similar mode of action can be predicted by the concentration Á/addition model as proposed by Anderson and Weber (1975).…”
Section: Introductionmentioning
confidence: 99%
“…Interaction of metals may be influenced by the tested species, the combination of metals and water quality (Otitoloju, 2002;Kungolos et al, 2009). Spehar and Fiandt (1986) indicated that the same combination of metals (arsenic, cadmium, chromium, copper, mercury and lead) showed different interactive effects depending on both the species exposed and the endpoint tested. Utgikar et al (2004) reported that the toxic effects of binary mixtures were substantially higher than simple addition of toxicity of the individual metals.…”
Section: Discussionmentioning
confidence: 99%